Spindle Bearing Preload Control Using NI MyRIO - Paweł Turek (Applied Sciences)
The article presents an application for controlling the preload of bearings in a model spindle system. The bearing preload will be implemented using piezoelectric elements, which allow for changing the preload of bearings during spindle operation, which results in a change in the stiffness of the entire system. Such a change in stiffness allows for effective reduction of the vibration amplitudes of the spindle tip. The use of the MyRIO 1900 device from National Instruments, which was programmed using LabVIEW 2021 SP1 (32 bit), is described in detail. The effectiveness of the control algorithm was confirmed on the basis of actual measurements of the vibration amplitude of the front spindle tip on which three different substitute masses (model grinding wheels) were placed. The values for the system without and with the operating control system were compared. The results were recorded five times for each state of the device and each substitute mass. The value of the maximum amplitude was taken into account after averaging it from all five tests without control and with control. The effectiveness of the control algorithm was the greater the heavier the substitute mass, which allowed for reducing the vibration amplitude by up to 20%.